Preliminary Study on the Role of Audit Opinions on Annual Budget Appropriation Outcomes for National Government Agencies (NGAs) in the Philippines - Placido, Remvert Bryan (Philippine Management Review; Vol 31 (2024), 2024)
Annual audit reports from the Commission on Audit (COA) provide information on a government agency’s compliance with financial reporting standards that may be valuable to government budget legislators and decision makers. Using Chi-square test of independence and logistic regression analysis on the available empirical data, we test whether COA audit reports, as represented by COA audit opinions, have a statistically significant association with government budget appropriation decisions, represented by year-on-year movements on the new general appropriations for National Government Agencies (NGAs). Based on the results, majority of the COA audit opinions issued for fiscal periods within the Duterte Administration (2016-2022) do not display a statistically significant association with the year-on-year movements of the budget appropriations. For the audit opinion years that showed a statistically significant association from the Chi-square test of independence, the correlation between COA audit opinions and year-on-year movements of the budget appropriations were found to be weak. Insights from an audit report should somehow, to a certain degree, affect the increases or decreases in budget allocation. Particularly, much attention should be given to government agencies who receive negative audit reports as these reports may point out misstatements in the financial statement that could potentially be instances of misappropriation of government assets.